Efecto de la colocación de dispositivos elásticos de hule, en las manos superiores del racimo de banano, sobre la conformación de la mano, el rechazo de frutos y la relación cajas-racimo - Vargas, Alfonso (2025)
Effect of rubber plastic bands, placed on banana’s bunch upper hands, on the conformation of the hand, the rejection of fruits and the relationship boxes-bunch. The effect of rubber elastic bands (REB) placed on the newly exposed 5 upper hands of the banana bunch was evaluated, from December 2006 to April 2008, on the conformation of the hand, the rejection of fruits and the number of boxes per bunch (‘ratio’). REB lasted 4 to 6 (experiment 1), 6 to 8 (experiments 2 and 3), 6 to 8 and more than 8 (experiment 4) and more than 8 (experiment 5) weeks. Bunches without REB were used as the untreated control treatment. In most hands where REB was tested, the curvature of the fruit did not differ (p>0.0934) and the distance (at 90 degrees) from the apex of the inner-row central fruit of the hand to the rachis remained unchanged (p>0.0672), as compared with the control. Nevertheless, when in the latter variable differences were expressed (p<0.0414), a reduction of the distance with de use of REB was always observed. The percentage of deformed fruits, except for the highest value (p<0.0389) of some hands in experiments 1, 2, 3 and 5, did not differ between treatments (p>0.0627). The different factors of fruit rejection, especially those related to deformity or injuries by friction between fingers during growth (growth scar), were not affected by the use of REB in any of the experiments where this was evaluated. The number of boxes obtained from the 5 upper hands of the bunch did not allow to show whether REB significantly affected yield.